Hubungan Antosianin dan Diabetes Melitus Tipe 2 dalam Kajian Medis - Martony, Oslida; Doloksaribu, Bernike; Hamid, Mansoor Abdul; Harahap, Armansyah Maulana; Alfira, Alfira (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of the current research is to review and provide a more comprehensive assessment of the relationship between the anti-diabetic effects of Anthocyanins in humans, whether consumed as a dietary supplement, purifying agent, flavonoid mixture, or extract. In this narrative review, eighteen recent clinical studies that have been published over the last five years studying the therapeutic effects of Anthocyanins in the diet in diabetes are described. Research results show that anthocyanin supplements can control blood glucose, glycated hemoglobin and other diabetes markers. Additionally, larger doses of Anthocyanins were shown to have better effects on diabetes treatment. There is evidence in this review that diets rich in Anthocyanins may increase the risk of diabetes, especially in people at risk. Additionally, research should focus on various clinical biomarkers, the ideal time frame for intervention, and the effect of Anthocyanins in both controlled and uncontrolled diabetes patients. In conclusion, clinical studies show that Anthocyanins can influence many targets related to diabetes mellitus simultaneously. Additionally, use of ACN during diabetes or hyperglycemia appears to be safe and effective. Keywords: Diabetes, Anthocyanin, Metabolism, Food